EFEKTIVITAS DEMONSTRASI EDUKASI PENGURANGAN PLAK GIGI DENGAN DAN TANPA LARUTAN PEWARNA PADA SISWA - Haryani, Nike; Halimah, Halimah; Damhuji, Damhuji; Herlina, Rita (Media Penelitian dan Pengembangan Kesehatan, 2025)
Education is a deliberate effort to influence individuals or groups to achieve optimal learning objectives. In dental health, the demonstration method is used to teach proper toothbrushing techniques for removing plaque. However, the effectiveness of this method can be influenced by the patient's awareness of plaque presence, which can be enhanced through disclosing solutions as educational tools. This study aims to evaluate the effectiveness of plaque reduction using the demonstration method with and without disclosing solutions. The study employed a pre-experimental design with a pre-post observational approach and statistical analysis using paired t-tests and independent t-tests. The research subjects consisted of 60 elementary school students from SDN 37, selected through purposive sampling. The paired t-test results indicated a significant difference in plaque index before and after education (p<0.05). However, the independent t-test showed no significant difference between the groups using disclosing solutions and those without (p>0.05). In conclusion, the demonstration method is effective in reducing plaque among students, both with and without disclosing solutions, although there is no significant difference in effectiveness between the two methods